Continuous Ambulatory Peritoneal Dialysis in Children: Experience from a Tertiary Care center of Bangladesh - Mamun, Abdullah Al; Rahman, Md. Habibur; Jesmin, Tahmina; Huque, Saimul; Begum, Afroza; Uddin, Golam Muin; Roy, Ranjit Ranjan (Journal of Pediatric Nephrology, 2020)
Background: Continuous ambulatory peritoneal dialysis (CAPD) is the most commonly used modality of renal replacement therapy (RRT) in children in different parts of the world. There is a paucity of published experience of CAPD in children from developing countries and also from Bangladesh. Methods: We retrospectively studied children with end-stage renal disease (ESRD) that had been on CAPD from January 2014 to December 2018 in a tertiary care center of Bangladesh, over the past 5 years. The objective was to assess the clinical and biochemical profile, complications encountered and outcome of children on maintenance CAPD. Result: Seven patients with ESRD were analyzed, mean age was 103months (range 28-168 month), 4 were male and three were female. CAPD was done in 2014 to a 7year old girl and subsequently 6 patients underwent CAPD. Outcome analysis of CAPD showed that only 6 episodes of peritonitis occurred among these 7 patients. Their follow up parameters showed that they are performing very well in context of growth, biochemical parameters and albumin level but one patients died due to sepsis and poor adherence. Conclusion: It can be concluded from these series of CAPD patients that CAPD could be a good choice of RRT in children in Bangladesh. It can reduce the uremic features as well as improve health status